Molecular basis of the adaption of the anchovy isolate Lactobacillus sakei CRL1756 to salted environments through a proteomic approach - Belfiore, Carolina (2013)
Osmotic stress triggered by high salt concentrations results in the injury of starters during food processing. The adaption of the anchovy isolate Lactobacillus sakei CRL1756 to salted environments in the presence of osmoprotectants was analyzed by using a proteomic approach. Glycine–betaine (GB) pre-treated cells exposed to 1.7 M NaCl+3 mM GB showed improved adaption achieving growth after a long lag phase while non-proliferative cells in the salted medium without GB was observed. Comparative proteomic analyses of the Lactobacillus cells grown in MRS+GB exposed or not to 10% salt revealed eighteen significantly regulated proteins. Under hypertonic stress, decreased synthesis of four glycolytic enzymes (Fba, Pgk, Gpm5, Tpi) and induction of other two (MleS, Pox2) related to an alternative energetic pathway, were registered. Proteins related to general stress response and nucleotide metabolism were up-regulated. Noticeably, the induction of DyP-type peroxidase, involved in iron transport, detoxification and oxidative stress, was observed for the first time in lactic acid bacteria under osmotic constraint. Our results demonstrate that GB played a significant role in protecting L. sakei CRL1756 against salt stress. Indeed, GB commonly found in marine fish may be used by the starter culture cells ensuring their robustness in salted-anchovy based products.